Key Performance Indicators of Vocational Education and Training in the Construction Industry - Isik, Zeynep; Budayan, Cenk; Aladag, Hande; Demirdogen, Gokhan; Yilmaz, Tamer; Arditi, David (TURKISH CHAMBER CIVIL ENGINEERS, 2019)
Considering the project-based nature of the construction industry, the success of a project is expected to affect the success of a company and in turn, the success of the industry. Vocational education and training (VET) can also be considered as a significant component of project success in the construction industry. Training the construction workers is likely to enhance the performance of construction projects by reducing the rework on site. The objective of the study was to have a comparative analysis of the Key Performance Indicators (KPIs) of the VETs of four countries (Germany, Netherlands, Lithuania, and Turkey). The KPIs of VET institutions in the construction industry were identified using the financial, trainee satisfaction, internal process, and learning and growth perspectives of the Balanced Scorecard (BSC). The KPIs were rated in workshops conducted in aforementioned countries. The data collected were analyzed by using Fuzzy Analytical Hierarchy Process (FAHP). This study fills the gap in the literature by identifying the KPIs of VET, and developing a performance measurement system of VET institutions in the construction industry. Considering that VET is a significant component of project success in the construction industry, performance improvement of VET institutions are expected to enhance the performance of construction projects and construction companies.
Keywords: performance management; performance improvement; key performance indicator (KPI); vocational training; construction industry; fuzzy analytical hierarchy process (FAHP); ANALYTIC NETWORK PROCESS; BALANCED SCORECARD; Engineering